Program MBKM: Meningkatkan Soft Skills Mahasiswa Program Studi Pendidikan Biologi - Novita Rahman; Erwing Erwing; Romi Adiansyah; Astuti Muh. Amin (IAIN Ternate, 2022)
Independent campus is the Merdeka Learning Campus Merdeka (MBKM) program organized by the Ministry of Education and Culture. This study aims to determine whether through MBKM the soft-skills of biology education study program students have increased. this research is a type of quantitative descriptive research. data collection techniques in the form of questionnaires distributed to biology education study program students who take part in the MBKM program. The results showed that the existence of MBKM activities had a good impact on improving the hard-skills and soft-skills of students, which could be seen from a number of respondents' answers, namely: 1) the ability to follow the MBKM program online; 2) the ability to adapt to new friends; 3) the ability to discuss, collaborate, provide advice in teams/groups; 4) the ability to use technological media; 5) the ability to analyze problems and solve problems in teams/groups; 6) the ability to make decisions with consideration of comparing opinions with one another; 7) the ability to follow the rules in MBKM activities as an attitude to improve learning discipline, besides that the improvement of hard-skills and soft-skills through the MBKM program can be seen in the Student Report obtained after the MBKM program is completed which lists the competency scores of hard-skills and soft-skills. Keywords: Biology Education Study Program Students, Merdeka Learning Merdeka Campus (MBKM), Soft Skills